2016
DOI: 10.1002/ajim.22670
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychosocial work factors and psychological distress on self‐assessed work ability: A 7‐year follow‐up in a general working population

Abstract: Strategies for sustainable work ability should focus on both working conditions and health factors. Am. J. Ind. Med. 60:121-130, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
2
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 46 publications
3
24
2
5
Order By: Relevance
“…The present results show consistencies with other studies. We found that number of physical disorders diagnosed by a physician predicted present and future work ability (e.g., van der Vijfeijke et al, 2013) and that emotional distress is an independent factor associated with work ability (e.g., Leijon et al, 2017; Martimo, Varonen, Husman, & Viikari-Juntura, 2007). Specifically, we found that depression symptoms predicted present and future work ability.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The present results show consistencies with other studies. We found that number of physical disorders diagnosed by a physician predicted present and future work ability (e.g., van der Vijfeijke et al, 2013) and that emotional distress is an independent factor associated with work ability (e.g., Leijon et al, 2017; Martimo, Varonen, Husman, & Viikari-Juntura, 2007). Specifically, we found that depression symptoms predicted present and future work ability.…”
Section: Discussionmentioning
confidence: 96%
“…The WAI has been criticised on theoretical grounds, as it consists of a combination of factors that do not seem to form a single dimension of work ability as intended (Martus, Jakob, Rose, Seibt, & Freude, 2010; Radkiewicz, Widerszal-Bazyl, & NEXT-Study Group, 2005). However, several studies have shown that using single items from the WAI offer reliable indicators of work ability and have approximately the same predictive validity as the whole scale (Ahlstrom et al, 2010; Kinnunen & Nätti, 2018; Leijon et al, 2017; Lindberg et al, 2009; Lundin et al, 2017; Roelen et al, 2014). Among its items, the item on individuals’ own evaluation of their work ability compared with lifetime best (work ability scale; WAS) is most commonly used.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological distress is a serious public health problem that affects college students [1][2][3] and the general working population 4 . These symptoms are disabling and can harm students' school performance and workers' ability to perform their functions 4,5 . Kessler et al 6 showed that developed countries were most affected by mental illness.…”
Section: Introductionmentioning
confidence: 99%